Duality Of Iterative Soft Dilation In Multi Scale Soft Morphological Environment (International Journal of Engineering and Computer Science, 2018)
In this paper,  duality is discussed in soft dilation in multi scale  as well as iterative environment. Soft erosion and soft dilation will exist for various thresholds.  So soft  open and soft close also exist for various thresholds. If definition for soft erosion and soft dilation are studied (5), then some type of equalities are viewed among soft morphological operations. So equality may be established in between soft erosion and soft dilation in multi scale environment.  open and  close are composite operations.  So soft open and soft close are also composite operations which will exist at various thresholds. Equality may be viewed among all soft morphological operations. In the same way  duality also will exist   for all soft morphological operations because duality will exist for all morphological operatons,for example dual of erosion is dilation ,dual of dilation is erosion,dual of open is close and dual of close is open. In this paper, duality is discussed in soft erosion operations,in multi scale as well as iterative environment..  A very important point is that equality does not exist in mathematical morphology but will exist in soft mathematical morphology. So various duals will occur for each soft morphological operation